Rethinking use and trade of pelagic sharks from Brazil - Barreto, R. R.; Bornatowski, H.; Motta, F. S. [UNESP]; Santander-Neto, J.; Vianna, G. M. S.; Lessa, R. (Elsevier B.V., 2017)
Brazil currently ranks as the 11th producer and 1st importer of shark meat around the world. Data available from the FAO software FishStatJ along with data from regional sources, such as governmental bulletins, scientific papers, gray literature and internet were revisited to identify the main issues surrounding pelagic shark fisheries, trade and consumption in the largest country in South America. Among the main findings, it was noted that Brazil has not properly collected fishery statistics since 2007, that many species of threatened sharks are freely landed and traded even though it is prohibited by local legislation and/or international recommendations (regional fisheries management organizations). The blue shark (Prionace glauca) is the most frequently recorded shark in the official bulletins and is currently a locally targeted species. Additionally, the significant imports of this species from 23 other countries that also provide fins for Asia has drawn attention in recent decades. Regarding consumption, shark is considered to be low-value seafood compared to more common fish, such as groupers and snappers, and most Brazilians actually do not know that they are eating sharks. At present, the proportion of threatened elasmobranchs (in which sharks are included) in Brazil (33%, of 145 species) exceeds the global rate identified for the group (25%), and, until the present moment, no measure related to the management of species has been implemented. As advice, Brazil urgently needs to restructure its fishery information collection systems, management strategies and to tighten sanitary and labeling regulations for the marketing of fish.